Extreme value statistics of 2D Gaussian free field: effect of finite domains. (10th December 2015) - Cao, X; Rosso, A; Santachiara, R
Abstract: We study minima statistics of the 2D Gaussian free field (GFF) on circles in the unit disk with Dirichlet boundary condition. Free energy distributions of the associated random energy models are exactly calculated in the high temperature phase, and shown to satisfy the duality property, which enables us to predict the minima distribution by assuming the freezing scenario. Numerical tests are provided. Related questions concerning the GFF on a sphere are also considered.